Space matters: reducing energy disparity in Nepal through spatially equitable renewable energy subsidies. (1st October 2022) - Bharadwaj, Bishal; Pattanayak, Subhrendu K; Ashworth, Peta
Abstract: Affordability is a major barrier to the adoption of clean energy technologies in low-income countries, which is partly why many governments provide subsidies to offset some of the upfront (installation) costs. However, simple administrative rules might not fully account for economic geography, resulting in lower subsidies for remote areas. Using regression analysis on a rich dataset of adoption, cost and subsidy for about 4000 Nepalese Village Development Committees over 22 years, we show that administratively determined lumpsum subsidies disproportionately hurt remote communities. Simulations show that adjusting the subsidy spatially to reflect the geographic cost of living, can increase clean technology adoption. Thus, spatial targeting of subsidies is key to accelerating energy access in remote settings such as the Hindu Kush Himalaya.